Tournamen Belajar antar Tim (Tobat) sebagai Upaya Peningkatan Pembelajaran Matakuliah Administrasi Pendidikan Jasmani - Suhadi, Suhadi (Jurnal Pendidikan Jasmani Indonesia, 2015)
This research is intended to know the effort of improvement for the study of the subject of the administration of physical education, in the Physical Education, Health, and Recreation (PJKR) Department, Faculty of Sport Science (FIK), Yogyakarta State University (UNY). This research uses the method of Classroom Action Research with two cyclical actions. The first cycle consists of 4 times meetings, which is later evaluated and reflected for the action of the second cycle. The second cycle contains 4 times meetings. Process of giving actions is equal in its step to the first cycle. Subject of this research is students of the 5th semester of the Physical Education, Health, and Recreation (PJKR) Department, FIK, UNY who are going through the subject of the administration of physical education in 2004, amounting to 35 persons. Setting of actions is conducted in the class during one semester (12 times of meetings). Instruments' arrangement is in accord with the observation guidance made by the researcher himself. The perceptions' agreement with the collaborator is done through information's exchanges and discussions. Based on the analysis in the course of study, hence it can be concluded that the Learning Tournament of Teams (TOBAT)'s pattern, indeed, can improve the learning process of the study of the administration of physical education, PJKR Department, FIK, UNY. This improvement is visible: students' motivation, students' participation in attending the course, students' cooperation in solving problems, more dynamic and conductively class atmosphere, and increasingly active participation of the lecturers. Keyword: Learning, The Administration of Physical Education.